In Vivo Evaluation of Customized Aortic Repair Using a Novel Survival Model. Issue 2 (August 2016) - Doorschodt, B.M.; Brom, H.L.; de Vries, A.C.; Meers, C.; Jacobs, M.J.
Abstract : Objective: The aim of the study was to evaluate the feasibility and mid-term biological behavior of the novel customized aortic repair (CAR) method for endovascular aneurysm treatment. Methods: CAR consists of exclusion of an aneurysm from the circulation using a custom-designed dog bone-shaped balloon, followed by aneurysm sac filling with an in situ curing polymer. After curing and balloon deflation, the circulation is restored through a patent cast neolumen. A liquid two-component polymer was injected via a small bore catheter under X-ray control into a surgically created aneurysm. In 50% of the procedures, a self expanding bare metal stent was placed in the polymer cast lumen. A novel animal model was established involving creation of an aneurysm by anastomosing a venous interposition graft into the common carotid artery of eight adult sheep. Two animals were excluded because of non-device related complications. The remaining six animals were monitored for 20 weeks with duplex sonograms performed monthly to assess blood flow and polymer cast lumen patency. After the animals were sacrificed the polymer cast, common carotid artery, and the brain in the carotid outflow tract were removed for histological assessment. Results: In four of the six animals, the aneurysm was successfully excluded using CAR with uneventful follow up. The aneurysm sac was filled incompletely in two animals, resulting in a stent malpositioning and cast lumen occlusion after 12 weeks in one case, and a type 1 endoleak in the other. All six animals survived for 20 weeks. Neither migration nor expansion of the polymer cast was observed and the polymer was demonstrated to be biocompatible and non-thrombogenic. Polymer emboli were not detected in the brain or meninges after sacrifice. Conclusions: The feasibility and mid-term biological safety of the CAR method for minimally invasive aneurysm repair was demonstrated using a simulated aneurysm survival model.